The environmental sustainability as a mediated variable in the risk management effect on the maritime pollution: case study of Iraqi seaport company - Edan, Abdul Rahman; Sultan , Wafaa (The Gulf Economist, 2024)
Abstract: The study aims to test the effect of marine risk management in the marine vessels as an independent variable on marine pollution in marine vessels as a dependent variable through the mediating variable of environmental sustainability in the Iraqi Ports Company. To achieve these goals, a hypothetical model was formulated. It consists of three variables that express the nature of the relationships between the variables. Four main hypotheses were deduced, with a set of sub-hypotheses branching out from each hypothesis. The descriptive analytical approach was adopted. The study sample consists of (260) employees in maritime cadres working in the Iraqi Ports Company. Data were collected using a questionnaire, and the statistical programs were used (AMOS, V.24) and (SPSS.V.26). The study reached several results, including the existence of a significant and statistically significant influence relationship between risk management and marine pollution. The study concluded that environmental sustainability mediates the relationship between risk management in marine vessels and environmental pollution. Based on the results, several conclusions and recommendations have been developed and formulated, including that there must be a specialized risk management in the Iraqi Ports Company whose mission is to identify, analyze, evaluate, and control risks to reduce the effects of pollution resulting from marine vessels and preserve environmental resources to achieve environmental sustainability.